Randomized clinical trial of stapler hepatectomy versus LigaSureTM transection in elective hepatic resection - Fritzmann, Johannes; Ulrich, Alexis; Knebel, Phillip; Mehrabi, Arianeb; Büchler, Markus W.; Rahbari, Nuh Nabi; Reißfelder, Christoph (The British journal of surgery, 2018)
Background Previous studies have demonstrated stapler hepatectomy and use of various energy devices to be safe alternatives to the clamp-crushing technique in elective hepatic resection. In this randomized trial, the effectiveness and safety of stapler hepatectomy were compared with those of parenchymal transection with the LigaSure™ vessel sealing system. Method Patients scheduled for elective liver resection at two tertiary-care centres were randomized during surgery to stapler hepatectomy or transection with the LigaSure™ device. Total intraoperative blood loss was the primary efficacy endpoint. Transection time, duration of operation, perioperative complications and length of hospital stay were recorded as secondary endpoints. Results A total of 138 patients were analysed, 69 in the LigaSure™ and 69 in the stapler hepatectomy group. Baseline characteristics were well balanced between the groups. Mean intraoperative blood loss was significantly higher in the LigaSure™ group than the stapler hepatectomy group: 1101 (95 per cent c.i. 915 to 1287) versus 961 (752 to 1170) ml (P = 0·028). The parenchymal transection time was significantly shorter in the stapler group (P = 0·005), as was the total duration of operation (P = 0·027). Surgical morbidity did not differ between the groups, nor did the grade of complications. Conclusion Stapler hepatectomy was associated with reduced blood loss and a shorter duration of operation than the LigaSure™ device for parenchymal transection in elective partial hepatectomy. Registration number: NCT01858987 (http://www.clinicaltrials.gov).
Im Titel ist "TM" hochgestellt
Gesehen am 26.07.2019